Comparação entre potenciais de água no solo, medidos no campo e simulados - Martinez , Mauro Aparecido; Ferreira , Paulo Afonso; Bernardo , Salassier; Nonato de Miranda Chaves , Raimundo (Revista Ceres, 2025)
A field experiment on a clay soil was undertaken in which water movement, introduced at a uniform rate of 62.5 cm3/hr, irrigated from a single isolated trickle emitter, was observed.